International child law - Akhtar, Rajnaara; Nyamutata, Conrad (London ; New York : Routledge, 2020)
"This book examines the rights of the child using the global framework of the United Nations International Convention on the Rights of the Child 1989. Analysing both public and private international legal aspects, this cross-disciplinary text promotes a holistic understanding of the on-going development of child law, children's rights and the protection of the child. In depth analysis of the following topic areas are included: Childhood in the Digital Age, Child Labour, International Parental Child Abduction, Inter-country Adoption, Child Sexual Exploitation, Children in Armed Conflict, and Indigenous Children. These topics are contextualised with further chapters on the concept of childhood and children's rights, the international legal framework in which the Convention operates and a substantive chapter on the Convention itself. This 4th edition has been updated and revised, including a new chapter dealing with issues arising from childhood in the age of unprecedented digital technological advancements; a crucial issue for childhood experiences in modern times. This edition also includes new case studies, recent legal developments in the field of international child law, and inclusion of broader scholarship to capture diverse views on international law and child law"--
Childhood and children's rights -- Introduction to international law sources and institutions -- The United Nations Convention on the Rights of the Child -- Childhood in the digital age -- Child labour -- International parental child abduction -- Inter-country adoption -- Child sexual exploitation -- Children in armed conflict -- Indigenous children.
Includes bibliographical references and index.
Keywords: Convention on the Rights of the Child -- (1989 November 20); Convention on the Rights of the Child; Convention on the rights of the child; Children (International law); Children -- Legal status, laws, etc; Children's rights; Children (International law); Children -- Legal status, laws, etc; Children's rights